MODERN TECHNOLOGIES OF SURFACE STRENGTHENING AND RESTORATION OF AVIATION EQUIPMENT PARTS - Кудрін, A. П.; Лабунець, В.Ф. (Proceedings of National Aviation University (archive), 2021)
Modern methods of surface hardening and restoration of aircraft parts are considered. It is shown that comtex methods allow to control the tribotechnical characteristics of coatings in a wide range of external factors, which ensures the efficiency of parts, their reliability and durability.